Implementasi Kebijakan Sertifikasi Guru dalam Pengembangan Pendidikan Agama Islam di MIS Kulu Kabupaten Nagan Raya - Miftahul Jannah; Silahuddin (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
This research aims to determine the implementation of teacher certification policies in supporting the development of Islamic religious education at MIS Kulu, Nagan Raya Regency. This study uses a descriptive qualitative approach to analyze data objectively based on field findings. The teacher certification policy is one of the government's efforts to improve the quality of education, including in Islamic Religious Education subjects. The main objective of this policy is to ensure that teachers have sufficient qualifications and competencies to provide effective learning. This research focuses on the implementation of certification policies in the development of Islamic religious education at the Kulu Private Madrasah Ibtidaiyah, Nagan Raya Regency, and its impact on the quality of learning. Data collection was carried out through interviews, observation and document analysis. Research findings reveal that teacher certification contributes significantly to improving the professional competence of teaching staff, which has a positive impact on the quality of Islamic religious education in these madrasas. However, there are still obstacles such as the need for further training, improving facilities, and the readiness of teaching staff to undergo the certification process which require further attention.